Dinamika Usaha Kecil dan Menengah (UKM) Analisis Konsentrasi Regional UKM di Indonesia 1999 – 2001 - Dyah Ratih Sulistyastuti (Economic Journal of Emerging Markets, 2004)
Small and Medium Enterprises (SMEs) are the most relevant topic to be discussed in Indonesia because of their significant contribution to the economic development in this country. The important role of SMEs in Indonesia is not only limited as job provider for the vast majority of the people, but also very vital in combating poverty, reducing unemploy¬ment, distributing income, and increasing non-oil export. The role of SMEs becomes even higher along with the emerging of autonomy era and globalization. While SMEs were seen only as job provider in the past, nowadays, SMEs are hoped can give more significant con¬tribution in enhancing non-oil export and provide input for the large-scale industries as sub¬contractor. This study is aimed to understand the dynamics of SMEs in Indonesia between 1999-2001. The analysis in this study will be focused to identify the concentration patterns and the growth of SMEs. The data used in this study are secondary data which were obtained from the Bureau of Statisics. The instruments of analysis employed in this study consist of concentration index and geographic information system. This study found that the growth of SMEs in Indonesia has not been distributed equally across the country. SMEs have been found in a very high concentration in several provinces; meanwhile they are less concen¬trated in the majority of the provinces. Keywords: SMEs, analysis of regional concentration.